Polyamic acid resin and transparent polyimide film using the same
By introducing polyside siloxane and cyclic amine/acid dianhydride copolymerization into the polyamino acid resin, transparent polyester ester material is formed, and the problem of insufficient optical and mechanical properties in the prior art is solved, and a covering window material suitable for flexible display equipment is realized.
Patent Information
- Application Number
- JP2023103286
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-20
- Filing Date
- 2023-06-23
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2043-06-23
AI Technical Summary
The prior art is difficult to provide a covering window material that has excellent optical and mechanical properties and is suitable for flexible display devices.
A polyamic acid resin containing polyhedral silsesquioxane (POSS) as a component is used to form a transparent polyimide film with excellent optical and mechanical properties by copolymerization with cyclic amines and acid dianhydrides.
It realizes high-gloss transmissive mittance, low yellowness and excellent mechanical properties, and is suitable for the covering window material of flexible display equipment.
Smart Images

Figure 0007659592000001 
Figure 0007659592000002 
Figure 0007659592000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamic acid resin and a transparent polyimide film using the same, and more particularly to a polyamic acid resin that can be used as a cover window for a display by simultaneously ensuring excellent optical properties and mechanical properties through the formation of an organic-inorganic hybrid by including a polyhedral silsesquioxane as a constituent component of the polyamic acid composition, and a transparent polyimide film using the same. [Background technology]
[0002] A cover window is applied to the surface of a display device such as a liquid crystal display (LCD), an organic light emitting display (OLED), etc., to protect the panel. Conventionally, tempered glass has been mainly used as a material for the cover window, because it has excellent flatness, heat resistance, chemical resistance, and barrier performance against moisture and gas, a small coefficient of linear expansion (CTE), and high light transmittance.
[0003] In recent years, flexible displays such as curved displays and in-folding displays have been developed. In order to be applicable to such flexible displays, the cover window must also have flexibility, but conventional cover windows made of glass materials are heavy, easily broken, and lack flexibility, making them unsuitable for flexible displays.
[0004] In order to solve the above problems, a cover window using a plastic material with a relatively high degree of freedom in molding has been proposed recently. A cover window using a plastic material has advantages of being light, not easily broken, and allowing various designs to be realized. Currently, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, etc., which have excellent transparency, are mainly used as plastic materials for cover windows. Although these materials have the advantage of excellent transparency, their glass transition temperature (Tg) is 150° C. or less, and they have poor heat resistance, low chemical resistance, and low mechanical strength, so that their application is limited. In addition, the cover window is disposed at the outermost periphery of the flexible display device, and if the above-mentioned materials are continuously exposed to external ultraviolet rays, a yellowing phenomenon occurs, which adversely affects the visibility of the display.
[0005] Currently, polyimide resin is used as a cover window material. Such polyimide resin has a limitation that it is difficult to ensure transparency because it is dark brown due to the formation of CTC (Charge Transfer Complex) of Pi electrons in the imide chain, and polyimide films containing this resin have the disadvantage that the surface is easily scratched and has very low scratch resistance. In particular, cover windows made of polyimide resin have the flexibility of the polyimide material itself, but they are prone to fatigue failure due to the generation and propagation of cracks caused by repeated stress and deformation, so research and development is needed to further improve the physical properties and lifespan of the material. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been devised to solve the above-mentioned problems, and has as its technical object to provide a novel polyimide film that has excellent physical properties such as transparency, mechanical properties, and thermal properties by forming an organic-inorganic hybrid and can be used as a cover window.
[0007] Other objects and advantages of the present invention will be more clearly explained based on the accompanying detailed description and claims. [Means for solving the problem]
[0008] In order to achieve the above-mentioned technical objectives, the present invention provides a polyamic acid resin copolymerized with at least one diamine; at least one acid dianhydride; and polyhedral oligomeric silsesquioxane (POSS); wherein at least one of the diamine and the acid dianhydride contains an alicyclic compound.
[0009] In one embodiment of the present invention, the polyamic acid resin is applicable for forming a transparent polyimide film.
[0010] In one embodiment of the present invention, the polyhedral silsesquioxane is contained in an amount ranging from 0.1 to 15% by weight relative to 100% by weight of the total solid content of the polyamic acid resin.
[0011] In one embodiment of the present invention, the polyhedral silsesquioxane is contained in an amount of 0.1 to 7 mol % relative to 100 mol % of the diamine or acid dianhydride.
[0012] In one embodiment of the present invention, the alicyclic compound includes at least one of an alicyclic diamine and an alicyclic acid dianhydride, and is included in a proportion of 10 to 100 mol % based on the total mol % of the diamine and the acid dianhydride combined.
[0013] In one embodiment of the present invention, the alicyclic acid dianhydride is contained in a proportion of 10 to 100 mol % based on the total mol % of the acid dianhydride.
[0014] In one embodiment of the present invention, the at least one acid dianhydride may further include one or more aromatic acid dianhydrides selected from the group consisting of fluorinated aromatic first acid dianhydrides, non-fluorinated aromatic second acid dianhydrides, and sulfonic aromatic third acid dianhydrides.
[0015] In one embodiment of the present invention, the at least one diamine may include an aromatic diamine, an alicyclic diamine, or a combination of an aromatic diamine and an alicyclic diamine.
[0016] In one embodiment of the present invention, the aromatic diamine and the alicyclic diamine are contained in a ratio of 0-100:100-0 mol % relative to 100 mol % of the total diamines.
[0017] In one embodiment of the present invention, the aromatic diamine may include at least one selected from the group consisting of a fluorinated first diamine, a sulfone-based second diamine, a hydroxyl-based third diamine, an ether-based fourth diamine, and a non-fluorine-based fifth diamine.
[0018] In one embodiment of the present invention, the molar ratio (a / b) of the diamine (a) to the acid dianhydride (b) may be in the range of 0.7 to 1.3.
[0019] The present invention also provides a transparent polyimide film which contains the above polyamic acid resin and is imidized.
[0020] In one embodiment of the present invention, the transparent polyimide film may have a transmittance of 85% or more at a wavelength of 550 nm when the film has a thickness of 30 to 100 μm, and a yellowness index (YI) according to the ASTM E313-73 standard of 5 or less.
[0021] In one embodiment of the present invention, the transparent polyimide film may have a Young's Modulus of 3 to 8 GPa measured in accordance with ASTM D882 and a pencil hardness of 2H to 5H.
[0022] In one embodiment of the present invention, the transparent polyimide film can be used as a cover window for a display device. Effect of the Invention
[0023] According to one embodiment of the present invention, polyhedral silsesquioxane is used as one of the reactants constituting a polyamic acid resin, and thus, an organic-inorganic hybrid is formed, which simultaneously exhibits high light transmittance, low yellowness, and excellent mechanical properties.
[0024] As a result, a transparent polyimide film using the above-mentioned polyamic acid resin can be usefully used as a cover window for display devices in the relevant field, such as flat display panels, flexible displays, and can also be applied to other well-known IT products, electronic products, home appliances, etc.
[0025] The effects of the present invention are not limited to the above-mentioned examples, and more diverse effects are included in the present specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described in detail below. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art, and the following examples can be modified in various ways, and the scope of the present invention is not limited to the following examples. In addition, the same reference numerals refer to the same structures throughout the specification.
[0027] Unless otherwise defined, all terms, including technical and scientific terms, used herein have the same meaning as commonly understood by those skilled in the art. Furthermore, terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant field, and should not be interpreted as idealized or overly formal unless expressly defined herein.
[0028] In addition, throughout the specification, when a part "includes" a certain component, it does not mean excluding other components, but may further include other components, unless otherwise specified. In addition, throughout the specification, "above" or "above" means not only the case where it is located above or below the target part, but also the case where there is another part in between, and does not necessarily mean that it is located above with respect to the direction of gravity. In addition, in this specification, terms such as "first", "second", etc. are used to distinguish components from each other, rather than indicating any order or importance.
[0029] <Polyamic acid resin> In one embodiment of the present invention, a polyimide precursor [poly(amic acid), PAA] polymer for producing a transparent polyimide film is provided, specifically, a polyamic acid resin containing polyhedral silsesquioxane in the repeat unit.
[0030] More specifically, the polyamic acid resin is copolymerized containing at least one diamine; at least one acid dianhydride; and polyhedral silsesquioxane (POSS); and at least one of the diamine and the acid dianhydride comprises an alicyclic compound.
[0031] That is, in the past, silsesquioxanes have been added to improve the physical properties of polyimides, but such silsesquioxanes have mostly been added in the form of fillers or mixed with polyamic acid resins or polyimide resins that have already been polymerized.
[0032] In contrast, the present invention uses polyhedral silsesquioxane as one of the reactants of the composition for producing polyamic acid. Specifically, the silsesquioxane contains at least one amino group at its end, which is involved in the reaction between diamine and dianhydride to form an additional chemical bond within the molecule, thereby producing a polyamic acid resin that is stronger and more rigid and has a higher molecular weight than conventional polyamic acids having a linear structure. Such polyamic acid resin is not decomposed by heat or light and is more stable against external impacts, so that the optical properties, thermal properties, and mechanical properties (modulus, strength), etc. of the transparent polyimide resin produced using the polyamic acid can be significantly improved.
[0033] The polyhedral silsesquioxane contained in the polyamic acid resin according to the present invention contains, in its basic skeleton, at least one of ordinary silsesquioxane structural units known in the art, such as M units, D units, T units, and Q units.
[0034] Here, the term "M unit" refers to a siloxane structural unit containing a silicon atom and one oxygen atom adjacent thereto, for example, RSiO 1 / 2 The term "D unit" refers to a siloxane unit containing a silicon atom and two oxygen atoms adjacent thereto (i.e., a linear siloxane unit), for example, RSiO 2 / 2 The term "T unit" refers to a siloxane unit having a silicon atom and three oxygen atoms adjacent thereto, for example, RSiO 3 / 2 The term "Q unit" refers to a siloxane unit having a silicon atom and four adjacent oxygen atoms, for example, SiO 4 / 2 The siloxane unit is represented by the formula:
[0035] In one specific example, the polyhedral silsesquioxane can be represented by the following Chemical Formula 1. [ka]
[0036] In the above formula, A is a group derived from a polyhedral silsesquioxane; X's are the same or different and are each independently selected from the group consisting of -CH2-, -(CH3)2C-, -SO2-, -(CF3)2C-, -CO-, and -CONH-; n is an integer of 0 or 1, Y are the same or different, and each independently represents C6 to C 30 Aryl groups of C3 to C 30 or which can be joined together to form a fused ring, The aryl group and the cycloalkyl group may each be independently substituted with one or more substituents selected from the group consisting of halogen, -CF3, and -OH, and when there are a plurality of the substituents, they may be the same or different.
[0037] In one specific example, the polyhedral silsesquioxane can be represented by the following chemical formula 2. [ka]
[0038] In the above formula, The R's may be the same or different, and each independently represent a C6 to C 30 Aryl groups of C3 to C 60 or which can be joined together to form a fused ring, The aryl group and the cycloalkyl group may each be independently substituted with one or more substituents selected from the group consisting of halogen, -CF3, -OH, and an amine group, and when there are a plurality of the substituents, they may be the same or different.
[0039] According to one embodiment of the present invention, A, X, and Y in Chemical Formula 1 can be more specifically represented by Chemical Formula 3 below. [ka]
[0040] The polyhedral silsesquioxane of the present invention is [RSiO 3 / 2 ] and does not contain other substituents such as epoxy groups. Such T units refer to silsesquioxane building blocks containing a silicon atom and three oxygen atoms adjacent thereto, and may be derived from a condensate of a hydrolyzate of a trifunctional silane compound and / or a silane compound having three hydrolyzable groups, for example. As an example, a conventional alkyltrialkoxysilane, aryltrialkoxysilane, or a mixture thereof known in the art can be used. Examples of usable alkyltrialkoxysilanes include, but are not limited to, methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, propylethyltrimethoxysilane, or a mixture thereof. Examples of usable aryltrialkoxysilanes include, but are not limited to, phenyltrimethoxysilane, phenyltriethoxysilane, naphthyltrimethoxysilane, naphthyltriethoxysilane, naphthyltrippropoxysilane, or a mixture thereof.
[0041] In one embodiment, the polyhedral silsesquioxane is [RSiO 3 / 2 % of the structural unit (T unit) represented by the formula:
[0042] In the present invention, the amount of polyhedral silsesquioxane used is not particularly limited, and for example, it can be contained in the range of 0.1 to 7 mol% relative to 100 mol% of the diamine or acid dianhydride, specifically, it can be in the range of 0.1 to 5 mol%, preferably 0.5 to 5 mol%. If the content of polyhedral silsesquioxane is within the above range, a polyamic acid resin having a more robust chemical structure and a high molecular weight is formed, and if such polyhedral silsesquioxane is out of the above range, a certain amount or more of the silsesquioxane reacts with the polyamic acid resin to form multiple bonds, which causes gelation (see Table 2 below).
[0043] The polyamic acid resin according to the present invention comprises at least one diamine and at least one acid dianhydride known in the art, at least one of which is copolymerized with an alicyclic compound.
[0044] In the present invention, the alicyclic compound may contain at least one of a common alicyclic diamine and an alicyclic acid dianhydride known in the art. Such alicyclic diamine and alicyclic acid dianhydride are not particularly limited as long as they contain at least one alicyclic ring in the molecular structure, and may be, for example, a component of an alicyclic diamine or alicyclic acid dianhydride as described below. Specifically, the alicyclic compound is an alicyclic acid dianhydride, and more specifically, it is preferable to use an alicyclic acid dianhydride represented by Chemical Formula 4 or Chemical Formula 5. Such an alicyclic compound may be contained in a ratio of 10 to 100 mol %, specifically, 50 to 90 mol %, based on 200 mol % of 100 mol % of diamine and 100 mol % of acid dianhydride, based on the total mol % of the diamine and acid dianhydride.
[0045] The diamine (a) component constituting the polyamic acid resin of the present invention is not particularly limited as long as it has a diamine structure in the molecule, and any ordinary diamine known in the art can be used without limitation. For example, aromatic, alicyclic, or aliphatic compounds having a diamine structure, or combinations thereof, can be used.
[0046] In particular, in the present invention, in consideration of the optical properties of the polyimide film, such as low reflectance, high light transmittance, and low YI, at least one alicyclic diamine may be used alone, or at least one aromatic diamine may be used, or the aromatic diamine and the alicyclic diamine may be used in combination.
[0047] As specific examples of the aromatic diamines described above, fluorine-based, sulfone-based, hydroxyl-based, ether-based, non-fluorine-based diamines having a fluorinated substituent can be used alone or in appropriate combinations of one or more.Therefore, in the present invention, as diamine compounds, fluorinated aromatic first diamines having a fluorinated substituent, sulfone-based aromatic second diamines, hydroxyl-based aromatic third diamines, ether-based aromatic fourth diamines, and non-fluorine-based aromatic fifth diamines can be used alone or in combination of two or more of them.
[0048] Examples of the diamine monomer (a) that can be used include 4,4'-oxydianiline (ODA), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (2,2'-TFDB), 2,2'-bis(trifluoromethyl)-4,3'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-5,5'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether (6-FODA), 2,2-bis(3-amino-4-hydroxyphenyl) Examples of the fluoroalkyl group include, but are not limited to, hexafluoropropane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (4BDAF), 2,2'-bis[4-(4-aminophenoxy)phenyl]propane (6HMDA), 4,4'-bis(3-aminophenoxy)diphenyl sulfone (DBSDA), bis(4-aminophenyl)sulfone (4,4'-DDS), bis(3-aminophenyl)sulfone (3,3'-DDS), or a mixture of one or more of these.
[0049] Considering the high transparency, high glass transition temperature, and low yellowness of polyimide films, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (2,2'-TFDB) and 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (6-FAPB), which can induce linear polymerization, were selected as the fluorinated first diamines. , or 2,2-bis(3-amino-4-methylphenyl)-hexafluoropropane (BIS-AT-AF) As the sulfone-based second diamine, bis(4-aminophenyl)sulfone (4,4'-DDS) or 3,3'-DDS can be used. As the hydroxyl-based third diamine, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (BIS-AP-AF) can be used. As the ether-based fourth diamine, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether (6-FODA) or oxydianiline (ODA) can be used. As the non-fluorine-based fifth diamine, t,m -toluidine (m-tolidine), or p-phenylenediamine (p-PDA) can be used.
[0050] In the diamine monomer (a) of the present invention, the content of the above-mentioned fluorinated aromatic first diamine, sulfone-based aromatic second diamine, hydroxyl-based aromatic third diamine, ether-based fourth diamine, non-fluorinated aromatic fifth diamine, alicyclic diamine, etc. is not particularly limited, and may be 0-100 mol%, specifically 10-90 mol%, more specifically 20-80 mol%, based on 100 mol% of the total diamines. However, the content of at least one of the above diamines is included in the remainder so as to satisfy 100 mol% of the total diamines.
[0051] Examples of alicyclic diamines that can be used include, but are not limited to, 2,2-bis(3-amino-4-hydroxycyclohexyl)hexafluoropropane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane (MACM), 4,4'-methylenebicyclohexylamine (PACM), 1,3-bis(aminomethyl)cyclohexane (1,3-BAC), 1,4-bis(aminomethyl)cyclohexane (1,4-BAC), cis-1,2-cyclohexanedimethaneamine, trans-1,2-cyclohexanedimethaneamine, 1,4-cyclohexyldiamine (CHDA), bis(4-aminocyclohexyl)ether, and mixtures thereof.
[0052] In the diamine monomer (a), the mixing ratio of the aromatic diamine and the alicyclic diamine is 0-100:100:-0 mol %, specifically, 10-90:90-10 mol %, relative to 100 mol % of the total diamines.
[0053] The dianhydride (b) monomer constituting the polyamic acid resin of the present invention can be any ordinary compound known in the art having a dianhydride structure in the molecule without any restrictions. For example, aromatic, alicyclic, aliphatic compounds having a dianhydride structure, or combinations thereof, can be used, and specifically, at least one alicyclic dianhydride can be used, or at least one aromatic dianhydride can be used, or the aromatic dianhydride and the alicyclic dianhydride can be used in combination.
[0054] The alicyclic acid dianhydride is not particularly limited as long as it is a compound that has an alicyclic ring that is not an aromatic ring and has an acid dianhydride. Specifically, it is preferable to use an alicyclic acid dianhydride represented by the following chemical formula 4 or 5. [ka] [ka]
[0055] In the above formula, A, B, and C are the same or different and each independently represents a cyclic alicyclic organic group having 4 to 20 carbon atoms; X is -O-, -S-, -C(=O)-, -CH(OH)-, -S(=O)2-, -(CH2) p -(where 1≦p≦10), -(CF2) q -(wherein 1≦q≦10), -(CH3)2C-, -(CF3)2C-, and -C(═OH)NH-; n is 0 to 2.
[0056] In a preferred example of the above Chemical Formula 4 or Chemical Formula 5, A to C may be the same or different and each independently represent a cyclic alicyclic organic group having 4 to 8 carbon atoms; X is selected from the group consisting of -CH2-, -(CH3)2C-, -SO2-, -(CF3)2C-, -CO-, and -CONH-; and n is 0 or 1.
[0057] Examples of the usable alicyclic acid dianhydride include cyclobutane tetracarboxylic dianhydride (CBDA), 1,2,3,4-cyclopentane tetracarboxylic dianhydride (CPDA), bicyclo[2,2,2]-7-octene-2,3,5,6-tetracarboxylic dianhydride (BCDA), 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride (TDA), 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic dianhydride (H-BPDA), 1,2,4,5-cyclohexane-tetracarboxylic dianhydride (H-PMDA), and cyclopentanone. Examples of the alicyclic dianhydride include, but are not limited to, bis-spironorbornane (cpODA), bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic acid 2,3:5,6-dianhydride (7CI,8CI), or a mixture of one or more of these. The content of such alicyclic dianhydride is not particularly limited, and can be appropriately adjusted in consideration of the mechanical properties and retardation properties of the polyimide film. As an example, the content of the alicyclic dianhydride can be 10 to 100 mol %, specifically 20 to 90 mol %, and more specifically 30 to 80 mol %, based on the total mol % of the dianhydride.
[0058] As a specific example of the aromatic acid dianhydride, a fluorinated aromatic first acid dianhydride, a non-fluorinated aromatic second acid dianhydride, and a sulfone-based aromatic third acid dianhydride may be used alone or in combination of at least two of them.
[0059] The fluorinated first dianhydride monomer is not particularly limited as long as it is an aromatic dianhydride having a fluorine substituent introduced therein. Examples of the fluorinated first dianhydride that can be used include, but are not limited to, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6-FDA) and 4-(trifluoromethyl)pyromellitic dianhydride (4-TFPMDA). These can be used alone or in combination of two or more. Among the fluorinated dianhydrides, 6-FDA is a compound that has a very high property of restricting the formation of charge transfer complexes (CTCs) between and within molecular chains, and is suitable for making the film transparent.
[0060] The non-fluorinated second acid dianhydride monomer is not particularly limited as long as it is a non-fluorinated aromatic acid dianhydride that does not have a fluorine substituent introduced therein. 2 Examples of the dianhydride monomer include, but are not limited to, pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), 4,4-(4,4-isopropylidenediphenoxy)bis(phthalic anhydride) (BPADA), bis(carboxyphenyl)dimethylsilane dianhydride (SiDA), etc. These may be used alone or in combination of two or more.
[0061] The sulfone-based third acid dianhydride monomer is not particularly limited as long as it is an acid dianhydride having a sulfone group introduced therein, and examples thereof include 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride (DSDA) and 4,4'-sulfonyldiphthalic acid anhydride (SO2DPA). These may be used alone or in combination of two or more.
[0062] In the acid dianhydride monomer (b) of the present invention, the content of the fluorinated aromatic first acid dianhydride, the non-fluorinated aromatic second acid dianhydride, the sulfone-based aromatic third acid dianhydride, etc. is not particularly limited. As an example, each of these can be contained in the range of 0 to 100 mol% relative to 100 mol% of the total acid dianhydride, specifically, 10 to 90 mol%, more specifically, 20 to 80 mol%. However, the content of at least one of the first acid dianhydride to the third acid dianhydride is included in the remainder so as to satisfy 100 mol% of the total acid dianhydride.
[0063] In the acid dianhydride monomer (b) according to the present invention, the mixing ratio of the aromatic acid dianhydride and the alicyclic acid dianhydride can be 0-90:10-100 mol %, specifically, 90-10:10-90 mol %, and more specifically, 80-10:20-90 mol %, relative to 100 mol % of the total acid dianhydrides.
[0064] In the composition for producing a polyamic acid constituting the polyamic acid resin of the present invention, the ratio (a / b) of the number of moles of the diamine component (a) to the number of moles of the acid dianhydride component (b) can be in the range of 0.7 to 1.3, preferably 0.8 to 1.2, and more preferably 0.9 to 1.1.
[0065] In addition, the polyamic acid production composition constituting the polyamic acid resin of the present invention can use any organic solvent known in the art as a solvent for the solution polymerization reaction of the above-mentioned monomers without any restrictions. As the usable solvent, for example, one or more polar solvents selected from m-cresol, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), acetone, diethyl acetate, and dimethylphthalate (DMP) can be used. In addition, a low boiling point solution such as tetrahydrofuran (THF) or chloroform, or a solvent such as γ-butyrolactone can be used. At this time, the content of the solvent (first solvent for polymerization) is not particularly limited, but in order to obtain an appropriate molecular weight and viscosity of the polyamic acid composition (polyamic acid solution), it can be preferably 50 to 95% by weight, more preferably 70 to 90% by weight, based on the total weight of the polyamic acid composition.
[0066] In the present invention, the dianhydride, diamine, and polyhedral silsesquioxane as described above are added to a solvent and then reacted to prepare a transparent polyamic acid composition. As an example, a transparent polyamic acid composition can be formed by including polyhedral silsesquioxane of Chemical Formula 1, at least one diamine component, and at least one dianhydride, and including diamine (a) and dianhydride (b) in an equivalent ratio of approximately 1:1 to improve the glass transition temperature and yellowness.
[0067] The composition of the polyamic acid composition is not particularly limited, and may be, for example, 2.5 to 25.0 wt% of dianhydride, 2.5 to 25.0 wt% of diamine, and the remainder of the organic solvent so as to satisfy 100 wt% of the composition, based on 100 wt% of the total solid content of the polyamic acid, and the polyhedral silsesquioxane may be contained in the range of 0.1 to 15 wt% based on 100 wt% of the total solid content of the polyamic acid. As an example, the content of the organic solvent may be 70 to 90 wt%.
[0068] The polyamic acid composition having the above-mentioned structure can have a viscosity in the range of about 1,000 to 200,000 cps, preferably about 5,000 to 50,000 cps. When the viscosity of the polyamic acid composition is within the above-mentioned range, the thickness can be easily adjusted when coating the polyamic acid composition, and the coating surface can be uniform.
[0069] If necessary, the polyamic acid composition may contain a small amount of at least one additive, such as a plasticizer, an antioxidant, a flame retardant, a dispersant, a viscosity modifier, or a leveling agent, within the scope of the object and effect of the present invention.
[0070] <Transparent polyimide film> In another embodiment of the present invention, there is provided a transparent polyimide film produced by imidizing the above-mentioned polyamic acid resin. Specifically, the transparent polyimide film is produced by imidizing a polyamic acid resin solution formed by solution polymerization of a polyamic acid composition containing a polyhedral silsesquioxane, followed by ring-closing dehydration at high temperature.
[0071] Such a transparent polyimide film can be incorporated into a display device, and more specifically, can be used as a cover window of a flexible display. Here, the cover window refers to a film disposed at the outermost edge of a flexible display device to protect the display device. Such a cover window can be a window film alone, or a film in which an adhesive layer and a window coating layer are provided on another substrate film made of an optically transparent resin.
[0072] In order to use the transparent polyimide film according to the present invention for the cover window of a mobile communication terminal, a tablet PC or the like, it is preferable that the polyimide film simultaneously has excellent optical properties such as high transparency and light transmittance as described above, and mechanical properties.
[0073] Specifically, the polyamic acid resin and polyimide film of the present invention contain at least one diamine, at least one acid dianhydride, and polyhedral silsesquioxane, and contain a repeating unit obtained by containing at least one alicyclic diamine or alicyclic acid dianhydride, and the polyhedral silsesquioxane contained in the repeating unit can be contained in the range of 0.1 to 15 wt% with respect to 100 wt% of the total solid content of the polyamic acid resin. By containing a specific alicyclic repeating unit obtained from such an alicyclic diamine / acid dianhydride, excellent visibility and mechanical properties can be ensured, and the silsesquioxane moiety contained in the repeating unit can significantly improve and optimize excellent mechanical properties such as high strength and high hardness.
[0074] In one specific example, the polyimide film has a light transmittance of 85% or more, specifically 89% or more, more specifically 90% to 99%, at a wavelength of 550 nm, when the film has a thickness of 30 to 100 μm. The yellowness index (YI) according to the ASTM E313 standard is 5 or less, specifically 4.7 or less, more specifically 4.5 or less. These optical properties are based on values measured under conditions where the polyimide film has a thickness of 30 to 100 μm, specifically 30 to 80 μm, specifically 40±5 μm.
[0075] In another specific example, the polyimide film may have a Young's Modulus of 3 to 8 GPa, specifically, 3 to 6 GPa. In order to simultaneously exhibit mechanical hardness and excellent flexibility, the Young's Modulus may be 4 to 6 GPa. Here, Young's Modulus is one of various moduli, and indicates the relative ratio when a material is loaded within its elastic limit, specifically, it means a value measured in accordance with ASTM D882. When the modulus value is smaller than the above-mentioned numerical value, it is difficult to fully exhibit hardness, and when the modulus value is larger than the above-mentioned numerical value, flexibility may decrease, and foldability may decrease.
[0076] In another specific example, the polyimide film has a thickness of 30 to 100 μm and an average coefficient of linear expansion (CTE) measured at 50 to 250° C. of 100 ppm / ° C. or less, specifically, 70 ppm / ° C. or less, more specifically, 30 to 65 ppm / ° C. or less.
[0077] The polyimide resin film according to the present invention can be produced by a conventional method well known in the art. For example, the polyamic acid composition as described above can be coated (cast) on a substrate, for example, a glass substrate, and then the temperature can be gradually increased within a range of 30 to 350° C. while inducing an imide ring-closing reaction for 0.5 to 8 hours.
[0078] In this case, the coating method may be any method known in the art, and may be at least one method selected from the group consisting of spin coating, dip coating, solvent casting, slot die coating, and spray coating. The polyamic acid composition may be coated at least once so that the colorless and transparent polyimide resin layer has a thickness of several hundreds of nm to several tens of μm.
[0079] In the method for producing a polyimide film according to the present invention, the imidization method applied in the step of casting the polymerized polyamic acid on a support and imidizing the same can be a thermal imidization method, a chemical imidization method, or a combination of the thermal imidization method and the chemical imidization method.
[0080] The thermal imidization method is a method in which a polyamic acid composition (polyamic acid solution) is cast onto a support and heated for 1 to 10 hours while gradually increasing the temperature within a temperature range of 30 to 400° C. to obtain a polyimide film.
[0081] The chemical imidization method is a method in which a dehydrating agent, such as an acid anhydride such as acetic anhydride, and an imidization catalyst, such as an amine such as isoquinoline, β-picoline, pyridine, etc. are added to a polyamic acid composition. When the thermal imidization method is used in combination with the chemical imidization method, the heating conditions for the polyamic acid composition can be changed depending on the type of polyamic acid composition, the thickness of the polyimide film to be produced, etc.
[0082] Regarding the case where the thermal imidization method and the chemical imidization method are used in combination, a dehydrating agent and an imidization catalyst are added to a polyamic acid composition, the composition is cast on a support, and the composition is then heated at 80 to 300° C., preferably 150 to 250° C., to activate the dehydrating agent and the imidization catalyst, whereby the composition is partially cured and dried, and then a polyimide film can be obtained.
[0083] The polyimide resin thus formed is a polymeric material containing an imide ring, and has excellent heat resistance, chemical resistance, abrasion resistance, and electrical properties due to the chemical stability of the imide ring. The polyimide resin may be in the form of a random copolymer or a block copolymer. The thickness of the polyimide film is not particularly limited and may be appropriately adjusted depending on the field of application. For example, it may be in the range of 10 to 15 μm, and preferably 30 to 100 μm.
[0084] The polyamic acid resin, polyimide film, and modified examples thereof prepared as described above according to the present invention can be usefully used in various fields requiring excellent optical properties such as high transmittance and yellowness, and mechanical properties such as high modulus. In particular, when applied to a cover window of a display device, the high hardness and strength prevent surface scratches, and provide a flexible display device with excellent visibility and high reliability. Such a display device can be applied to any display device known in the art without any restrictions, and in particular, can be an in-folding or out-folding type foldable display.
[0085] In the present invention, the display device refers to a flexible display device or a non-flexible display device that displays an image, and includes not only a flat panel display (FPD) device but also a curved display device, a foldable display device, a flexible display device, a foldable phone, a smartphone, a mobile communication terminal, a tablet computer, etc. Specifically, the display device includes a liquid crystal display, an electrophoretic display, an organic light emitting display, an inorganic light emitting display, a field emission display, a surface-conduction electron-emitter display, a plasma display, a cathode ray display, an electronic paper, etc. In one specific example, the display device may be a flat display panel such as an LCD, a PDP, or an OLED. The uses of the polyimide film of the present invention are not limited to those mentioned above, and it can be used in ordinary display devices known in the art, and can also be used as a substrate for flexible displays or a protective film.
[0086] In one embodiment of the display device including the polyimide film, the display device includes a display unit, a polarizing plate, a touch screen panel, a cover window, and a protective film, and the cover window may include the polyimide film according to one embodiment of the present invention. In addition, each component constituting the display device is not particularly limited and may include common components known in the art. EXAMPLES
[0087] The present invention will be described in detail below with reference to specific examples. The examples described below are merely illustrative to aid in understanding the present invention, and the scope of the present invention is not limited to these examples.
[0088] [Examples 1 to 16: Production of polyimide films] A polyamic acid composition was produced using a composition including diamines, acid dianhydrides, and polyhedral silsesquioxane (OAPS) of Chemical Formula 3, as shown in Table 1 below.
[0089] The polyamic acid composition was spin-coated on LCD glass, and then dried and imidized in a nitrogen atmosphere convection oven while gradually increasing the temperature stepwise: 80°C for 30 minutes, 150°C for 30 minutes, 200°C for 1 hour, and 300°C for 1 hour. This produced a polyimide film with a thickness of 40 μm and an imidization rate of 85% or more. The polyimide film was then peeled off and removed from the glass.
[0090] [Table 1]
[0091] [Comparative Examples 1 to 8: Production of Polyimide Films] Polyimide films of Comparative Examples 1 to 8 were produced in the same manner as in Examples 1 to 16 above, except that the compositions shown in Table 1 above were used.
[0092] [Comparative Example 9: Production of polyimide film] A polyamic acid resin was prepared by polymerizing the diamine and the acid dianhydride shown in Table 1 above. Next, polyhedral silsesquioxane (OAPS) represented by Chemical Formula 3 was added to the prepared polyamic acid resin and stirred for 12 hours to prepare a polyamic acid composition.
[0093] The polyamic acid composition was spin-coated on LCD glass, and then dried and imidized in a nitrogen atmosphere convection oven while gradually increasing the temperature stepwise: 80°C for 30 minutes, 150°C for 30 minutes, 200°C for 1 hour, and 300°C for 1 hour. This produced a polyimide film with a thickness of 40 μm and an imidization rate of 85% or more. The polyimide film was then peeled off and removed from the glass.
[0094] [Experimental example: Physical property evaluation] The physical properties of the polyimide films produced in Examples 1 to 16 and Comparative Examples 1 to 9 were evaluated by the following methods, and the results are shown in the following Table 2. Note that each physical property in the following Table 2 is based on a polyimide film having a thickness of 50 μm.
[0095] <Physical property evaluation method> 1) Measurement of light transmittance Measurements were made at a wavelength of 550 nm using a UV-Vis NIR spectrophotometer (Shimadzu, model number: uv-3150).
[0096] 2) Yellowness measurement The yellowness at 550 nm was measured using a spectrophotometer (manufactured by Konica Minolta, model number: CM-3700d) in accordance with the ASTM E313-73 standard.
[0097] 3) Thickness measurement The thickness of the film was measured using a film thickness gauge (manufactured by Mitutoyo Corporation, model number: 293-140).
[0098] 4) Measurement of modulus The modulus (GPa) was measured using a UTM (Instron, model number: 5942) in accordance with the ASTM D882 standard.
[0099] 5) Pencil hardness measurement The pencil hardness was measured using a pencil hardness tester with a load of 750 g according to the ISO 15184 standard.
[0100] [Table 2]
[0101] As shown in Table 2, the polyimide film of the present invention containing polyhedral silsesquioxane had excellent optical properties and mechanical properties compared to the comparative examples. In particular, the modulus properties tend to improve as the content of polyhedral silsesquioxane increases, but in Comparative Examples 2, 4, 6, and 8, in which the content of polyhedral silsesquioxane was 10 mol% and 7.5 mol%, respectively, the excessive amount of polyhedral silsesquioxane reacted with the polyamic acid resin, causing gelation, and no film was formed.
[0102] In addition, the polyimide film of Comparative Example 9, which was produced by first producing a polyamic acid resin and then adding polyhedral silsesquioxane, had poor optical properties and mechanical properties compared to Example 4, which had the same composition. This is because when polyhedral silsesquioxane is used as one of the reactants of a polyamic acid resin, a polyamic acid resin that is stronger and more rigid as well as has a higher molecular weight can be produced, which is believed to significantly improve the optical properties and mechanical properties of the polyimide resin.
[0103] Therefore, it was confirmed that the polyimide film of the present invention can be effectively used as a cover window for a display device.
Claims
1. A fluorinated aromatic first diamine: Dianhydrides, including aromatic and alicyclic dianhydrides; and Polyhedral silsesquioxanes (POSS); A polyamic acid resin for forming a transparent polyimide film, which is copolymerized with The polyhedral silsesquioxane is contained in an amount of 0.1 to 5 mol % relative to 100 mol % of the diamine, The alicyclic acid dianhydride is cyclobutane tetracarboxylic acid dianhydride (CBDA), the alicyclic acid dianhydride is contained in an amount of 70 to 90 mol % based on the total mol % of the acid dianhydride, A polyimide film formed using the polyamic acid resin has a transmittance of 85% or more at a wavelength of 550 nm when the film has a thickness of 30 to 100 μm, and a pencil hardness of 3H to 5H.
2. 2. The polyamic acid resin according to claim 1, wherein the polyhedral silsesquioxane is contained in an amount of 0.1 to 15% by weight relative to 100% by weight of the total solid content of the polyamic acid resin.
3. The polyamic acid resin according to claim 1 , wherein the polyhedral silsesquioxane is represented by the following chemical formula 1: 【Chemistry 1】 (In the above formula, A is a group derived from a polyhedral silsesquioxane; X's are the same or different and each independently represents -CH 2 -, -(CH 3 ) 2 C-, -SO 2 -, - (CF 3 ) 2 selected from the group consisting of -C-, -CO-, and -CONH-; Y are the same or different, and each independently represents C 6 ~C 30 and C 3 ~C 30 or which can be joined together to form a fused ring, The aryl group and the cycloalkyl group each independently represent a halogen, —CF 3 and -OH, and when there are a plurality of the above substituents, they may be the same or different from each other; n is an integer of 0 or 1.
4. 2. The polyamic acid resin according to claim 1, wherein the aromatic acid dianhydride further comprises one or more aromatic acid dianhydrides selected from the group consisting of a fluorinated aromatic first acid dianhydride, a non-fluorinated aromatic second acid dianhydride (wherein the non-fluorinated aromatic second acid dianhydride does not have a sulfone group), and a sulfone-based aromatic third acid dianhydride.
5. 2. The polyamic acid resin according to claim 1, wherein the molar ratio (a / b) of the diamine (a) to the acid dianhydride (b) is in the range of 0.7 to 1.
3.
6. A transparent polyimide film containing the polyamic acid resin according to any one of claims 1 to 5 and imidized.
7. At a film thickness of 30 to 100 μm, The transmittance at a wavelength of 550 nm is 85% or more, 7. The transparent polyimide film according to claim 6, which has a yellowness index of 5 or less.
8. The Young's Modulus measured in accordance with ASTM D882 is 3 to 8 GPa; 7. The transparent polyimide film according to claim 6, which has a pencil hardness of 3H to 5H.
9. The polyimide film according to claim 6, which is used as a cover window for a display device.
Citation Information
Patent Citations
Well-defined nanosized building blocks for organic / inorganic nanocomposites
JP2004529984A
Liquid crystal aligning agent and liquid crystal display element
JP2008203537A
Liquid crystal aligning agent, liquid crystal alignment layer, and liquid crystal display element
JP2010102159A
Polysiloxane compound and cured product thereof
JP2018145247A
Silsesquioxane-containing polyimide
JP2020033540A